Asymptomatic Pancreatic Perivascular Epithelial Cell Tumor (PEComa) in a Male Patient: Report and Literature Review - Zemet, Roni; Mazeh, Haggi; Neuman, Tzahi; Freund, Herbert R; Eid, Ahmed (JOP. Journal of the Pancreas, 2011)
Background Perivascular epithelial cell tumors (PEComas) are a family of rare mesenchymal neoplasms which share cellular, immunohistochemical and ultrastructural characteristics but are found in different visceral and soft tissue sites. PEComas of the pancreas are extremely rare neoplasms. Case report We describe a 49-year-old male who was incidentally diagnosed with a pancreatic mass. Endoscopic ultrasound-guided biopsy suggested a PEComa. An uneventful pylorus-preserving pancreaticoduodenectomy was thus performed. The tumor was a solid well-circumscribed mass in the pancreatic head with dilatation of the main pancreatic duct. Histopathology revealed a well-circumscribed and vascularized neoplasm, measuring 32x27x30 mm, composed of epithelioid smooth muscle cells with clear cytoplasm rich in glycogen. The tumor exhibited immunoreactivity to alpha-smooth muscle actin and to melanoma-associated antigen HMB-45. Conclusions Although rare, pancreatic PEComas should be included in the differential diagnosis of a pancreatic mass. Currently, the paucity of cases published makes it impossible to predict the behavior and prognosis of these tumors or to advocate an optimal therapy. Image: Positive immunoreactivity to melanoma-associated antigen HMB-45.